Legal Regulation of Extradition of Persons for Criminal Prosecution or Execution of a Sentence in the BRICS Member States and Candidate States - V. Karpovich (BRICS Law Journal)
This article analyzes the legal regulation of the extradition of persons for criminal prosecution or execution of a sentence in the BRICS states. The legal and technical features of the national legal regulations governing extradition in Brazil, India, China and South Africa are analyzed. It is noted that each of these nations (with the exception of Russia) has adopted a special law on extradition, which regulates in detail all procedural aspects of international cooperation in the field of the extradition of criminals. In addition, the legal regulation of the extradition of persons for criminal prosecution or execution of a sentence in the BRICS candidate states is also analyzed. In particular, this study provides both a general description of the countries’ legislation (the different legal systems) and an assessment of the national legal regulations governing extradition in each of the BRICS countries, including such countries as Iran, Argentina, Algeria, Bahrain and the UAE. The mechanisms of interstate and interdepartmental cooperation are deeply described. Furthermore, the prospects of international legal integration of the BRICS states in the field of extradition are assessed, taking into account the possible entry of the candidate states into the BRICS group. Following an analysis of the national legislation of both the BRICS member states and the BRICS candidate states, the idea of creating and adopting a “BRICS Convention on Extradition” is proposed.